The effect of increase isometric strength on technique during the front foot contact phase in elite cricket fast bowlers - Felton, P.; Shine, K.; Yeadon, M.; King, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The study investigates the effect of increased isometric strength on technique in elite male cricket fast bowlers. A 16-segment forward-dynamics simulation model individualised to investigate optimal technique of the front foot contact phase of fast bowling for ten elite male bowlers was utilised. For each individualised model, isometric strength was increased by 5%, technique (initial body configuration and subsequent movement) re-optimised, and the differences between the original and strengthened optimal techniques analysed. Ball release speed increased by-1) with a delay in bowling arm circumduction the only technique difference observed. No differences were found when comparing kinetic parameters. This suggests isometric strength does not limit technique in elite bowlers, this knowledge could influence elite coach development and applied practice